Peran moderasi halal lifestyle pada hubungan pengetahuan keuangan dan kepercayaan terhadap minat menabung masyarakat di bank syariah - Harisya, Syahda Malyavitha; Mochlasin, Mochlasin (Nur Science Institute, 2022)
The purpose of this study was to determine the effect of financial knowledge and trust on the interest of the millennial community in Semarang Regency to save in Islamic banks with the addition of a halal lifestyle as a moderating variable. This research is quantitative. This research uses the field research method. The samples used were 100 samples. The analysis method uses moderated regression analysis. The results of this study indicate that the financial knowledge variable has a positive but insignificant effect on people's interest in saving. The trust variable positively and significantly affects people's interest in saving. The halal lifestyle variable cannot moderate the influence of financial knowledge on people's interest in saving. The halal lifestyle variable cannot moderate the influence of trust on people's interest in saving.